2017
DOI: 10.1021/jacs.7b02229
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Removal of Endogenous Carbon Monoxide by Selective and Cell-Permeable Hemoprotein Model Complexes

Abstract: Carbon monoxide (CO) is produced in mammalian cells during heme metabolism and serves as an important signaling messenger. Here we report the bioactive properties of selective CO scavengers, hemoCD1 and its derivative R8-hemoCD1, which have the ability to detect and remove endogenous CO in cells. HemoCD1 is a supramolecular hemoprotein-model complex composed of 5,10,15,20-tetrakis(4-sulfonatophenyl)porphinatoiron(II) and a per-O-methylated β-cyclodextrin dimer having an pyridine linker. We demonstrate that hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 61 publications
1
50
0
Order By: Relevance
“…This could indicate that either HYCO-6 cannot enter the cell and deliver CO or that there is a different chemical reactivity of HYCO-3 and HYCO-6 towards COP-1, the probe we used to detect intracellular CO. Notably, we observed similar results using hemoCD, a unique CO scavenger that binds CO with high affinity and that allows the determination of intracellular CO levels [45] , [46] , confirming that only the manganese-containing HYCO-3, unlike its ruthenium-based counterpart (HYCO-6), delivers CO to cells at the concentrations used (data not shown, manuscript in preparation). This difference may also be explained by the increased bioavailability of HYCO-3, since we found that HYCO-3 is significantly more stable than HYCO-6 in plasma and microsomes.…”
Section: Discussionsupporting
confidence: 77%
“…This could indicate that either HYCO-6 cannot enter the cell and deliver CO or that there is a different chemical reactivity of HYCO-3 and HYCO-6 towards COP-1, the probe we used to detect intracellular CO. Notably, we observed similar results using hemoCD, a unique CO scavenger that binds CO with high affinity and that allows the determination of intracellular CO levels [45] , [46] , confirming that only the manganese-containing HYCO-3, unlike its ruthenium-based counterpart (HYCO-6), delivers CO to cells at the concentrations used (data not shown, manuscript in preparation). This difference may also be explained by the increased bioavailability of HYCO-3, since we found that HYCO-3 is significantly more stable than HYCO-6 in plasma and microsomes.…”
Section: Discussionsupporting
confidence: 77%
“…CO released into the vial headspace was quantified by gas chromatography. CO accumulated in cultured 3T3-L1 adipocytes after treatment with CORM-401 was measured spectrophotometrically using a specific scavenger of CO (hemoCD1) as previously described (48).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, the CO-binding affinity of hemoCD1 in aqueous solutions is the highest among the reported CO-binding hemoproteins. More advantageously, the NO-binding affinity of hemoCD1 is lower than that of hemoglobin 35 . The coordination strength of H 2 S to a hemoCD1 analog is also relatively weak, and the SH – ligand is easily replaceable with CO 36 .…”
Section: Introductionmentioning
confidence: 99%